Identifying osteoporotic vertebral endplate and cortex fractures - Wáng, Yì Xiáng J.; Santiago, Fernando Ruiz; Deng, Min; Nogueira-Barbosa, Marcello H. (Quantitative Imaging in Medicine and Surgery; Vol 7, No 5 (October 31, 2017): Quantitative Imaging in Medicine and Surgery, 2017)
Osteoporosis is the most common metabolic bone disease, and vertebral fractures (VFs) are the most common osteoporotic fracture. A single atraumatic VF may lead to the diagnosis of osteoporosis. Prevalent VFs increase the risk of future vertebral and non-vertebral osteoporotic fracture independent of bone mineral density (BMD). The accurate and clear reporting of VF is essential to ensure patients with osteoporosis receive appropriate treatment. Radiologist has a vital role in the diagnosis of this disease. Several morphometrical and radiological methods for detecting osteoporotic VF have been proposed, but there is no consensus regarding the definition of osteoporotic VF. A vertebra may fracture yet not ever result in measurable changes in radiographic height or area. To overcome these difficulties, algorithm-based qualitative approach (ABQ) was developed with a focus on the identification of change in the vertebral endplate. Evidence of endplate fracture (rather than variation in vertebral shape) is the primary indicator of osteoporotic fracture according to ABQ criteria. Other changes that may mimic osteoporotic fractures should be systemically excluded. It is also possible that vertebral cortex fracture may not initially occur in endplate. Particularly, vertebral cortex fracture can occur in anterior vertebral cortex without gross vertebral deformity (VD), or fractures deform the anterior vertebral cortex without endplate disruption. This article aims to serve as a teaching material for physicians or researchers to identify vertebral endplate/cortex fracture (ECF). Emphasis is particularly dedicated to identifying ECF which may not be associated apparent vertebral body collapse. We believe a combined approach based on standardized radiologic evaluation by experts and morphometry measurement is the most appropriate approach to detect and classify VFs.